Quantitative ethnomedicinal study of indigenous knowledge on medicinal plants used by the tribal communities of Central Kurram, Khyber Pakhtunkhwa, Pakistan - Hussain, Sayed; Hussain, Wahid; Nawaz, Ashiq; Badshah, Lal; Ali, Ashgar; Ullah, Shariat; Ali, Maroof; Hussain, Hidayat; Bussmann, Rainer W (Ethnobotany Research and Applications, 2022)
Background: The use of plants for different ethnobotanical purposes is a common practice in the remote areas of developing countries, particularly in reference to human and animal healthcare. For this aim, it is important to document ethnomedicinal use of plants for human and livestock healthcare from unexplored regions. Objective: The current study aimed to document the use of medicinal plants and to assess their conservation status. We hypothesized that Central Kurram, due to its remoteness and maintenance of traditions would show distinct differences in medicinal plant use in comparison to other areas of Pakistan. Method: The data was collected through semi-structured interviews and was analyzed using various quantitative indices including use value (UV), relative frequency of citation (RFC), use report (UR), fidelity level (FL), informant consensus factor (ICF) and family importance value (FIV). Plant samples were collected identified and then processed as voucher specimens following standard ethnobotanical practice. Results: One hundred twenty participants including 80 men and 40 women were interviewed. The participants reported a total of 106 plant species, belonging to 96 genera and 50 families. There were two families of pteridophytes (2 species), 2 families of gymnosperm (4 species) and 100 species belonging to 46 families of angiosperms. The local population used therapeutic plants to heal 114 different diseases in 19 aliment categories in the study area. A total of 106 species belonging to 50 families were documented as used to treat different types of illness. The UV ranged from 0.01 (Artemisia scoparia and Malva sylvestris) to 0.75 (Conyza canadensis). The RFC varied from 0.025 (Hyoscyamus niger and Senecio crysanthemoides) to 1.992 (Ephedra intermedia). The species with 100% FL were Astragalus stocksii and Artemisia scoparia, while the FCI ranged from 0 to 1 for insecticides and acoustic disorders. The conservation assessment revealed that 49 plant species were vulnerable, followed by rare (34 spp.), infrequent (7 spp.), Dominant (5spp.) And 5 endangered species. Conclusion: The current study showed that Central Kurram has a significant diversity of medicinal plant, and the use of medicinal plants and plant-based remedies is still common in the area. A total of 106 medicinal plant species, belonging to 50 families were documented for the treatment of 114 disorders. The residents used medicinal plants in treatment of important diseases such as Covid-19, cancer, dysentery, as diuretic, wound healing, and sexual diseases.